ANALISIS PENGGUNAAN VARIASI KATALIS NaOH, NaCl, DAN KOH TERHADAP LAJU ALIRAN GAS HHO - Prasetyo -; Raden Hengki Rahmanto; Jenny Primanita Diningrum (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2019)
Enhancement human need for energy, especially fossil energy that is used in everyday life as fuel in industry and fuel that is used for personal use. Increased consumption of fossil fuels is not offset by the availability of natural resources, therefore alternative energy is needed to reduce dependence on fossil fuels. One alternative energy that has been found is electrolysis of water to produce HHO gas. This study aims to determine the production rate and efficiency of the HHO gas generator using a variety of NaOH, NaCl and KOH catalysts where each catalyst uses a mass fraction percentage of 4.76%. From the results of the research that has been done the results of NaOH catalyst have a flow rate of 2.203 ml / s and are the best catalyst compared to 1.24 ml / s NaCl catalyst and 1.859 ml / s KOH catalyst. Then for efficiency, KOH catalyst was obtained as the best catalyst with an efficiency of 8.76% compared with NaCl of 8.18% and NaOH of 7.82%